Adaptive analysis of cortical plasticity with fMRI in full face and arm transplants - Şavklıyıldız, Ayhan; Özkan, Ömer; Uysal, Hilmi; Şenol, Utku; Özkan, Özlenen; Doğan, Ebru Apaydın; Barçın, Ebru; Bilge, İnci; Gök, Kadir; Döğer, Ela Naz; Şimşek, Buket; Carlak, Hamza Feza; et al. (Brain imaging and behavior, 2021)
The aim of this study is to examine cortical plasticity and to analyze cortical reorganization following hand and facial transplantation, using functional magnetic resonance imaging. Patients who had undergone full-face transplantation, hand transplantation and scapular arm replantation, as well as healthy controls, participated in the study. The perioral area and volar surfaces of the index finger and thumb were stimulated and images were acquired using 3 T functional MRI. The areas of the somatosensory cortex representing the hand and face are different in size and shape due to experience-dependent plasticity. Therefore, a new and more adaptive volume of interest analysis was created whereby the radiuses of the VOI masks were defined by the peak intensity of subsequent clusters. For each control subject, the distribution of activated voxels was observed for various cluster defining thresholds in order to determine the mean number of activated voxels for each stimulation inside the defined region. The determined numbers of voxels per subject were extracted from the defined regions using a binary search algorithm. Subsequently, the distances between the weighted centers of the extracted regions were calculated and compared. In transplant patients, the weighted centers of the hand and face clusters were separated at same-sized volumes. Two of the rehabilitated full-face transplant patients converge to the range of the controls. As a result, the weighted distribution of somatotopy indicated previous and present cortical reorganization. Additionally, referred sensation was assessed in two full-face transplant and one replant patient with activation clusters partially in BA40 in the Inferior Parietal Lobule.